A Semantic Analysis of Sentence, Utterance, and Presupposition in The Short Story “The Necklace” By Guy De Maupassant - Anggita Tiara Apriliani; Naila Rahmawati (INDO PUBLISHING, 2025)
This study explored the semantic components of presupposition, speech, and phrase in Guy de Maupassant's short story